2016
DOI: 10.18632/oncotarget.8988
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-beta-catenin pathway signals metastasis-associated tumor cell phenotypes in triple negative breast cancers

Abstract: Tumor cells acquire metastasis-associated (MA) phenotypes following genetic alterations in them which cause deregulation of different signaling pathways. Earlier, we reported that an upregulation of the Wnt-beta-catenin pathway (WP) is one of the genetic salient features of triple-negative breast cancer (TNBC), and WP signaling is associated with metastasis in TNBC. Using cBioPortal, here we found that collective % of alteration(s) in WP genes, CTNNB1, APC and DVL1 among breast-invasive-carcinomas was 21% as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
5
45
0
Order By: Relevance
“…In triple-negative breast cancer cells, the integrin-dependent metastasis-associated phenotypes are accompanied by the upregulation of Wnt/β-catenin pathway (De et al, 2016). The present study examined whether Cd could activate Wnt/β-catenin pathway without engaging integrins in the MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In triple-negative breast cancer cells, the integrin-dependent metastasis-associated phenotypes are accompanied by the upregulation of Wnt/β-catenin pathway (De et al, 2016). The present study examined whether Cd could activate Wnt/β-catenin pathway without engaging integrins in the MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Altered β-catenin expression/subcellular localization also plays a major role in EMT process in various malignancies including PrCa (6). Studies have suggested involvement of β‐catenin in the development, progression and therapy resistance of advanced PrCa (3).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the AR_CTNNB1 PPI essentiality rank percentile was very high in a number of cell lines including COLO704 ovarian (99%ile), and BT20 (98%ile) and MDA-MB-453 (97%ile) triple-negative breast cancer cell lines. Both Wnt [38] and androgen signaling [39] have been shown to be important in subsets of ovarian and triple-negative breast cancers [4042]. Another example of signaling crosstalk identified by this analysis is that of YAP1_CTNNB1 interactions in L363 myeloma cells (94%ile), CADO-ES1 Ewing’s sarcoma cells (96%ile), and A204 rhabdomyosarcoma cells (96%ile).…”
Section: Resultsmentioning
confidence: 93%